PENGARUH PENERAPAN KEPEMIMPINAN KLINIS TERHADAP KOMPETENSI PERAWAT DI RUMAH SAKIT: KAJIAN LITERATUR [THE EFFECT OF CLINICAL LEADERSHIP IMPLEMENTATION ON NURSE COMPETENCE IN HOSPITALS: A LITERATURE REVIEW] - Adria Novriani; Catharina Dwiana Wijayanti (Universitas Pelita Harapan, 2024)
Nurses who have less Clinical Leadership Competency can reduce the quality of service in a hospital to patients and even have a significant impact on patient safety. The study results showed that as many as 50% of new nurses have very limited knowledge of clinical leadership, namely in teamwork, as well as applying knowledge, practicing, and improving nursing services. In addition, nurses are also limited in their continuous personal development. This study aim was to determine the influence of the application of Clinical Leadership on nurse competency and the factors that influence the application of Clinical Leadership Competency This was a literature review study which used Google Scholar and Pubmed as the datebases. The research results show that a significant influence on the application of clinical leadership on the competency of nurses in hospitals. Where the application of clinical leadership will increase the competency of nurses and help create a positive culture for nurses regarding personal qualities; working with others, quality of nursing care management, improving service and the ability to act as a change agent. Apart from that, the application of clinical leadership is greatly influenced by nurses' self-leadership, experience, and training as well as hospital management. The application of clinical leadership can increase the competency of nurses in hospitals.BAHASA INDONESIA Perawat yang memiliki Clinical Leadership Competency kurang dapat mengurangi kualitas pelayanan di sebuah rumah sakit kepada pasien bahkan sangat berdampak pada keselamatan pasien. Hasil penelitian menunjukkan sebanyak 50% perawat baru memiliki pengetahuan tentang kepemimpinan klinis sangat terbatas yaitu dalam kerjasama dalam tim (team work), serta mengaplikasikan pengetahuan, praktik, serta peningkatan pelayanan keparawatan. Selain itu, perawat juga terbatas dalam pengembangan pribadi secara berkelanjutan Penelitian ini bertujuan untuk mengetahui pengaruh penerapan Clinical Leadership terhadap kompetensi perawat serta faktor-faktor yang mempengaruhi penerapan Clinical Leadership Competency. Metode penelitian ini adalah studi literature review. Database yang digunakan sebagai sumber literature terdiri dari Google Scholar, Pubmed. Science Direct dan Gale Cencag. Hasil penelitian menggambarkan bahwa adanya hubungan yang signfikan pada penerapan clinical leadership terhadap kompetensi perawat di rumah sakit. Penerapan clinical leadership akan meningkatkan kompetensi perawat dan sangat membantu terbentuknya budaya organisasi yang positif bagi perawat dalam hal kualitas diri; kemampuan bekerjasama dengan orang lain, kualitas manajemen asuhan keperawatan, pengembangan layanan dan kemampuan berperan sebagai change agent. Selain itu, dalam penerapannya clinical leadership sangat dipengaruhi oleh self-leadership perawat, pengalaman dan pelatihan serta managemen rumah sakit. Penerapan kepemimpinan klinis dapat meningkatkan kompetensi perawat di rumah sakit.